Mellan friskt och sjukt: Mindfulness som universalmedel - Eklöf, Jenny (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2015)
Mindfulness meditation started its academic career in the 1970s within behavioral medicine and mind-body research. Now, you find it in psychotherapy, neuroscience and clinical psychology, but also increasingly in the social sciences such as education, organization studies, social work and economics. Mindfulness meditation is offered as a secular program for healing, self-understanding and growth, and has moved from the cultural margins (Buddhism) to the mainstream, both scientifically and culturally. The variety of problems that mindfulness addresses is made possible by the fact that it actually spans both the pathological and the normal or healthy. In actual fact, it collapses that distinction regularly. By introducing readers, listeners or viewers to a mind that is “mindless” in its normal state – running on autopilot, being lost in thought, always in a doingmode – it simultaneously pathologizes people’s normal mode of functioning. Mindfulness proponents claim to work with universal and transdiagnostic processes, which underpin both health and sickness. Hence, anyone endowed with a mind benefits from mindfulness meditation. Mindfulness has been able to connect to and makes sense of collectively experienced societal changes, and offers scientifically grounded (albeit patchy) guidance on how to relate to these. The initial focus on stress related problems, evident in the name of its first medical institution – The stress reduction clinic – resonated with growing societal concerns over the downsides of multitasking and “workaholism” in the 1980s, 1990s and onwards.